Combined intensity and coherent change detection with four classes for laboratory multistatic polarimetric synthetic aperture radar - Alexander Hagelberg; Daniel Andre; Mark Finnis (IET Radar, Sonar & Navigation)
Abstract Satellites and drone swarms can be used to collect multistatic Synthetic Aperture Radar (SAR) images. Synthetic Aperture Radar images can be used for Intelligence Surveillance and Reconnaissance. One method is to use Coherent Change Detection (CCD) to identify changes such as objects or tracks in the scene. This paper investigates a two‐stage change detector, formed using intensity change and CCD images, extended to laboratory measured multistatic SAR data. A variety of performance metrics are used to quantitatively assess the results. Bistatic results are compared to a variety of multistatic and fully polarimetric results. The improvement in performance of multistatic and fully polarimetric images over bistatic images is shown. Additionally challenges and limitations of using multistatic datasets are highlighted.